Efeito da suplementação com tretinoína nanoencapsulada na produção in vitro de embriões bovinos - Lucas, Caroline Gomes (2014)
The possibility of increasing the genetic pattern and animal production make the in vitro production of embryos an extremely valuable technique for the technological development of livestock. However, due to the need for mimicking the in vivo process, that consists in several interdependent steps there are difficulties in setting the optimal conditions for each situation performed. The improvement of in vitro maturation (IVM) protocols through supplementation with different molecules can increase the efficiency of the culture medium and improve the competence of oocytes for fertilization and embryogenesis. A promising approach is the realization of mediated delivery of nanocarriers molecules. Tretinoin (TTN, all- trans retinoic acid - ATRA ) is a natural retinoid and active metabolite of vitamin A with important action in cell proliferation and differentiation and embryonic development under both in vivo and in vitro conditions. TTN acts on the cytoplasmic maturation process, in the initial embryonic development and oocyte competence, improving the quality of embryos generated. The combinations of tretinoin with polymeric nanoparticles are alternatives to enhance the solubility and chemical stability of this molecule, allowing controlled release and decreased degradation. The objective of this study was to evaluate the effects of IVM medium supplementation with tretinoin-loaded lipid-core nanocapsules (TTN-LNC) at concentrations of 0.25, 0.5 and 1 μM, by analysis of embryonic development until the blastocyst stage, production of reactive oxygen species (ROS), and expression of genes related to apoptosis and pluripotency. As main results, TTN-LNC 0.25 μM increased the rate of blastocyst production and reduced ROS production. In addition, TTN and TTN-LNC induced a lower gene expression of Bax and SHC1, suggesting beneficial effects on the development of embryos. The results indicate that nanoencapsulation allows the use of a lower dose of TTN-LNC with consequent obtention of higher percentages of blastocyst production and decreased production of ROS, making nanoembriology a potential tool for improving bovine embryos IVP.